Levels of burnout and its association with resilience and coping mechanisms among orthopaedic surgery residents: a single institution experience from Singapore - Sean WL Ho; Ernest BK Kwek (Singapore Medical Journal)
Introduction: Burnout has implications for surgeon wellbeing and patient care. We aimed to: (a) describe burnout levels among orthopaedic surgery residents in an Accreditation Council for Graduate Medical Education-International (ACGME-I) accredited programme; and (b) determine associations between burnout levels and resident characteristics, resilience and coping mechanisms. Methods: This is a grant-funded, cross-sectional questionnaire-based study that included 44 orthopaedic surgery residents. Burnout was measured using Maslach Burnout Inventory and resilience was determined using the Short Grit Scale. Coping mechanisms were determined using the Brief Coping Orientation to Problems Experienced scale. Results: 20 (45.5%) residents fulfilled the criteria for burnout. High levels of emotional exhaustion (EE) and depersonalisation (DP) correlated with stressors, such as inadequate sleep (EE: r = 0.43, P <0.01; DP: r = 0.33, P <0.05), conflict between family and work (EE: r = 0.40, P <0.01; DP: r = 0.40, P <0.01), financial pressure (DP: r = 0.46, P <0.01), and conflict with residents (EE: r = 0.35, P <0.05; DP: r = 0.34, P <0.05) and faculty (EE: r = 0.44, P <0.01; DP: r = 0.35, P<0.05). Severe burnout was associated with lower grit scores (p <0.05). Coping mechanisms, such as planning and positive reframing, were protective while behavioural disengagement and substance use may increase burnout risk. Conclusion: Burnout was high in our ACGME-I accredited programme. Stressors associated with higher burnout included feeling of inadequate sleep, poor work-life balance, poor relationships with fellow residents/faculty and financial pressures. Residents should be educated on protective coping mechanisms and regular screening to detect burnout should be performed.